ANALISIS RASIO KEUANGAN SEBAGAI PREDIKTOR PERUBAHAN LABA: Kasus Perusahaan Property dan Real Estate Yang Terdaftar PadaIndonesia Stock Exchange (IDX) Periode Tahun 2010â2012 - , ANGGUNO PUTRA YUNAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Profit is an important information regarding decision making. Profit in financial statement presents the value of last year profit, so user of financial statement analyzes the financial statement to earn information about profit in the future. Financial ratio analysis is a method used to calculate profit changes in the future. This research aims to verify that financial ratio can be used to predict the profit changes in property and real estate company listed in Indonesia Stock Exchange (IDX) on 2010-2012. Financial that is used in this research are current ratio, quick ratio, asset turnover, net profit margin, return on equity, debt to equity, longterm debt to equity, price earning ratio, and price to book value. The result of this research states that financial ratio used in this research simultanously effect on or could become a predictor of profit changes.Partially, return on equity ratio effect on or could become a predictor of profit changes.